1994
DOI: 10.1002/1520-6629(199410)22:4<312::aid-jcop2290220404>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Applying a stress and coping framework to research on mutual help organizations

Abstract: Few studies of mutual help have been guided by coherent conceptual frameworks. We introduce a stress and coping model that can guide research on self‐help groups and contribute to conceptualizing them as normative social groupings. Our model suggests that coping responses, life stressors, and social resources influence the processes by which persons become involved in mutual help organizations and, in turn, are influenced by involvement in mutual help. To provide initial empirical support for the model, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Several studies have suggested that AA involvement partially mediates the relationship between network support for drinking (Tonigan et al, 1996) and subsequent drinking outcomes (Humphreys et al, 1994;Longabaugh et al, 1998Longabaugh et al, , 2001. That is, individuals assigned to TSF have greater subsequent AA involvement compared with those assigned to CBT or MET, and it is the AA involvement that leads to better drinking outcomes by buffering the negative effects of social networks supportive of drinking.…”
Section: Limitations and Future Directionssupporting
confidence: 60%
“…Several studies have suggested that AA involvement partially mediates the relationship between network support for drinking (Tonigan et al, 1996) and subsequent drinking outcomes (Humphreys et al, 1994;Longabaugh et al, 1998Longabaugh et al, , 2001. That is, individuals assigned to TSF have greater subsequent AA involvement compared with those assigned to CBT or MET, and it is the AA involvement that leads to better drinking outcomes by buffering the negative effects of social networks supportive of drinking.…”
Section: Limitations and Future Directionssupporting
confidence: 60%
“…Some population studies show that women are more likely to drop out of AA/NA (Humphreys et al, 1994) and may not participate for reasons related to program structure, challenges related to lack childcare or if they sense AA/NA is punitive and male dominated (Kaskutas, 1994). Other studies demonstrate that while women may drop out of 12 step attendance more than men after 12 months of treatment (Humphreys et al, 1991), they were more likely to attend in the first place (Humphreys et al, 1994). However, in those studies, after the initial dropout period, women were found to attend as regularly as men (Humphreys et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrate that while women may drop out of 12 step attendance more than men after 12 months of treatment (Humphreys et al, 1991), they were more likely to attend in the first place (Humphreys et al, 1994). However, in those studies, after the initial dropout period, women were found to attend as regularly as men (Humphreys et al, 1994). Additionally gender and other sociodemographic variables have not been reliably found to be strongly associated with 12-step attendance in prior studies among general groups of substance abusers (Bogenschultz, 2008; Emrick et al, 1993; Tonigan et al, 1996) or among HIV+ substance users (Burnam et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Research has documented the benefits of 12-step participation in psychosocial functioning and recovery-promoting domains, including enhanced self-efficacy to resist temptations to use drugs and/or alcohol and motivation for abstinence (Kelly, Myers, & Brown, 2000;Morgenstern, Labouvie, McCrady, Kahler, & Frey, 1997), improved coping strategies (Humphreys, Finney J., & Moos RH. 1994;Humphreys, Moos, & Finney, 1996;Morgenstern et al, 1997;Timko, Finney, Moos, & Moos, 1995;Timko, Moos, Finney, & Lesar, 2000;Snow, Prochaska, & Rossi, 1994), improved social support and particularly social support for recovery (Humphreys & Noke, 1997;Humphreys et al, 1999), reduced psychological problems such as depression and anxiety (Gossop et al, 2003), lower stress (Laudet & White, 2008), higher quality of life (Gossop et al, 2003) and higher levels of life meaning and purpose (White & Laudet, 2006).…”
Section: Enhancing Recovery Capital: Participation In 12-step Fellowsmentioning
confidence: 99%